Qawaid Fiqihiyyah dan Peranannya dalam Pengembangan Hukum - Anton Kodim; Muannif Ridwan (Indra Institute Research & Publication, 2022)
This keyword is required for computerization. The search for research titles and abstracts is made easier by those key words This article is intended to examine Qowaid Fiqhiyyah and its role in the development of Islamic law. Qowaid Fiqhiyyah (fiqh rules) are rules formulated by scholars and mujtahids who are guided by the verses of the Qur'an and the Hadith of the Prophet in order to achieve the benefit of a problem that has not yet been determined. The basic sources of the formulation of Qowaid Fiqhiyyah are divided into two, namely the formal basis and the material basis. The role of Qowaid Fiqhiyyah in the development of Islamic law is as a guide that facilitates mujtahids and legal experts in making decisions related to legal issues. This is proven through several fatwas issued by the MUI as a result of the Ijtihad of the ulama. The method used in writing this article is a literature review method by reviewing and referring directly to primary and secondary references in the study of Qawaid Fiqhiyyah and its role in the development of Islamic law..